Diseminasi Pemanfaatan Pupuk Bionik Untuk Perbaikan Performa Pertumbuhan Rumput Laut - Pieter Amalo; Ni Putu Dian Kusuma; Lukas G.G. Serihollo; Rifqah Pratiwi (Yayasan Literasi Sains Indonesia, 2022)
Farming seaweed is a significant source of income since it helps coastal communities become more resilient. Due to the simple growing, harvesting, and drying methods, low degree of capital investment, and quick production cycle (1.5 months), seaweed cultivation in Tablolong Village, West Kupang District, East Nusa Tenggara Province is dominated by cultivators from coastal villages. The present issue for farmers of seaweed is the unavailability of seeds, both in terms of quantity and quality. Simple actions such as community service projects (PKM) with a focus on fertilizing activities utilizing bionic fertilizers can be taken to encourage the growth of seaweed. The method used to achieve the target of this PKM program is participatory counseling, dissemination of research results, assistance in seaweed cultivation, and monitoring during seaweed cultivation. In November 2021, PKM operations are conducted in Tablolong Village's coastal region. Through the use of bionic seaweed fertilizer, the activity's aim is to earn the partner group's production rates. After participating in PKM activities, the